9 YEAR BASIC EDUCATION POLICY - Jaja Abdul Jabar; Suheti; Supardi; Anis Fauzi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This article examines the 9-year basic education policy in Indonesia, which is an implementation of the 1945 Constitution to guarantee the right to education for all citizens. This policy aims to improve access and quality of education, improve the life of the nation, and create quality human resources. The review includes the history of the policy, starting from Law No. 4 of 1950 to the launch of the program by President Soeharto in 1984, as well as the influence of political interests and the modernization of Islamic education in the National Education System Law. The implementation of the policy involves a shared responsibility between the government, parents, and the community. Although it has been running, challenges such as low awareness of education and family economic conditions are still obstacles. Therefore, collaborative efforts and adequate funding are needed to ensure the provision of quality basic education, as well as open alternative education pathways. Sustainable policies such as the 12-year compulsory education program are expected to strengthen the foundation of education and increase access for future generations